Infectivity of gastric and intestinal Cryptosporidium species in immunocompetent Mongolian gerbils (Meriones unguiculatus) - Kvác, Martin; Sak, Bohumil; Kvetonová, Dana; Secor, W Evan (Veterinary parasitology, 2009)
We exposed juvenile (7-day old) and adult (8-week old) Mongolian gerbils (Meriones unguiculatus) to Cryptosporidium andersoni or C. muris, which infect the stomach, or to C. parvum, which infects the intestine. Both age groups could be successfully infected with each species in primary mono-infection with juvenile animals demonstrating higher peak oocysts per gram of feces and longer patent periods than adults. Concurrent exposure to mixed gastric and intestinal cryptosporidia resulted in successful infection with both species. The time course and infection intensities in the mixed infections were similar to those of primary mono-infection and for a given species. Similarly, sequential mixed infection of C. andersoni positive gerbils with C. muris 25 days after exposure to C. andersoni resulted in simultaneous infection with both gastric species. In contrast, following primary infection and clearance, animals re-exposed to the same Cryptosporidium species, failed to excrete oocysts in their feces and histological examination revealed no developmental stages in the stomach or intestine. In cross-infections, where the secondary exposure was with a different Cryptosporidium species than the initial cleared infection, successful infection was possible with a gastric species following C. parvum, or with C. parvum following a gastric species, but primary infection with one gastric species precluded secondary infection with the other gastric species. These results indicate cross-immunity between gastric Cryptosporidium species but not between intestinal and gastric species. Furthermore, our study demonstrates that Mongolian gerbils are susceptible to infection with many Cryptosporidium species and are a useful laboratory model for studies of mixed cryptosporidiosis.
Keywords: Aging; imunokompetence; Cryptosporidiosis; Mice; Cryptosporidium; Mice, Inbred BALB C; nemoci hlodavců; Gerbillinae; stárnutí; Disease Susceptibility; Rodent Diseases; náchylnost k nemoci; Immunocompetence; myši inbrední BALB C; Animals; kryptosporidióza; zvířata; myši